Clinical Reevaluation of the QuantiFERON TB-2G Test as a Diagnostic Method for Differentiating Active Tuberculosis from Nontuberculous Mycobacteriosis - Kobashi, Yoshihiro; Obase, Yasushi; Fukuda, Minoru; Yoshida, Kouichiro; Miyashita, Naoyuki; Oka, Mikio (Clinical infectious diseases, 2006)
Introduction. We reevaluated the usefulness of a whole-blood interferon-γ enzyme-linked immunosorbent assay (QuantiFERON TB-2G [QFT-TB]; Cellestis) in obtaining a differential diagnosis between active tuberculosis (TB) and nontuberculous mycobacteriosis (NTM). Methods.The subjects were 50 healthy volunteers, 50 patients with active TB, and 100 patients with NTM who satisfied the diagnostic guidelines of the American Thoracic Society from April 2005 through June 2006. The tuberculin skin test (TST) and the QFT-TB test were performed for all subjects. The QFT-TB test was performed every 2 months. Results. Of the healthy volunteers, 64% had a negative TST result and 94% had a negative QFT-TB test result. Of the patients with active TB, 64% had a positive TST result and 4% had a negative QFT-TB test result. Of the patients with pulmonary Mycobacterium avium complex disease, 60% had a positive TST result and 7% had a positive QFT-TB test result. The QFT-TB test had a mean sensitivity of 86% and a mean specificity of 94%. The QFT-TB test results for patients with active TB transiently decreased during treatment involving antituberculous drugs. The rate of positive QFT-TB test results was 86% at the initiation of treatment, 48% 6 months later, and 33% 12 months later. Conclusions. We confirmed that the QFT-TB test is a useful diagnostic method for differentiating active pulmonary TB from NTM, compared with the TST. However, because it is possible that the effect of the QFT-TB test may be long lasting after treatment and may not be resolved over time, even with treatment, as in this study, it may not provide any level of certainty regarding cure of infection.